The impact of regulatory reforms on cost structure, ownership and competition in Indian banking - Zhao, Tianshu; Casu, Barbara; Ferrari, Alessandra (Journal of Banking & Finance, 2010)
This paper evaluates the impact of financial sector reforms on the cost structure characteristics and on the ownership–cost efficiency relationship in Indian banking. It also examines the impact of reforms on the dynamics of competition in the lending market. We find evidence that deregulation improves banks performance and fosters competition in the lending market. Results suggest technological progress, once Indian commercial banks have adjusted to the new regulatory environment. This, however, does not translate in efficiency gains. There is also evidence of an ownership effect on the level and pattern of efficiency change. Finally, competition keeps building pace even in the re-regulation period and technological improvements are not hampered by the tightening of prudential norms.